2015
DOI: 10.1101/033555
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical Validation of a Non-Invasive Prenatal Test for Genome-Wide Detection of Fetal Copy Number Variants

Abstract: Abbreviations: bootstrap confidence level (BCL); chorionic villus sampling (CVS); 32 chromosomal abnormality decision tree (CADET); cell-free DNA (cfDNA); circular binary 33 segmentation (CBS); copy number variants (CNVs); non-invasive prenatal testing 34 (NIPT); sex chromosomal aneuploidies (SCAs); massively parallel sequencing (MPS), 35 triomsy 21 (T21); trisomy 18 (T18); trisomy 13 (T13) 36 ABSTRACT 38Background: Current cell-free DNA (cfDNA) assessment of fetal chromosomes does not 39 analyze and report… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…NIPT allows for the reliable detection of the common aneuploidies at high sensitivity (≥99% for trisomy 21, ≥92% for trisomy 18, and ≥87% for trisomy 13) and specificity (≥99% for trisomy 21, 18, and 13), even for low risk pregnancies . Broader applications of the technique for common microdeletions, genome wide screening, copy number variants, single gene disorders, and X linked disorders have recently been developed but these screening tests are characterized by significantly lower positive predictive values. Thus, expansion of the NIPT testing portfolio to a wider array of conditions recreates the initial problematic conditions of traditional first trimester screening in which patients were subjected to invasive testing at much higher rates.…”
Section: Introductionmentioning
confidence: 99%
“…NIPT allows for the reliable detection of the common aneuploidies at high sensitivity (≥99% for trisomy 21, ≥92% for trisomy 18, and ≥87% for trisomy 13) and specificity (≥99% for trisomy 21, 18, and 13), even for low risk pregnancies . Broader applications of the technique for common microdeletions, genome wide screening, copy number variants, single gene disorders, and X linked disorders have recently been developed but these screening tests are characterized by significantly lower positive predictive values. Thus, expansion of the NIPT testing portfolio to a wider array of conditions recreates the initial problematic conditions of traditional first trimester screening in which patients were subjected to invasive testing at much higher rates.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] To date, most clinical studies have either evaluated very small numbers of affected pregnancies or larger data sets without complete outcome information. [13][14][15][16][17][21][22][23][24][25][26][27] Ravi et al 16 described the performance of a targeted single nucleotide polymorphism (SNP)-based cfDNA test in a retrospective cohort study of 400 clinical samples with confirmed genetic status for 22q11.2. One false positive was identified, correlating to a specificity of 99.74%.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…1,11,12 The ability of cell-free DNA (cfDNA) analysis to detect fetal 22q11.2 deletions as early as the first trimester of pregnancy has been demonstrated in analytical validation studies and small cohorts. [13][14][15][16][17] However, professional societies have been reluctant to recommend screening because the clinical performance of cfDNA analysis for 22q11.2 deletions requires further investigation. [18][19][20] To date, no prospectively collected, large clinical validation study of prenatal cfDNA analysis for 22q11.2 deletions has been published.…”
Section: Introductionmentioning
confidence: 99%
“…NIPT has also evolved from exclusively trisomy 21 testing to include trisomy 18, trisomy 13, sex chromosome aneuploidies, and microdeletions. In 2016, one clinical validation study demonstrated that genome-wide NIPT could provide high resolution, sensitive, and specific detection of a wide range of fetal subchromosomal and whole chromosomal abnormalities that were previously only pinpointed by invasive karyotyping testing [67]. In some cases, this NIPT also provided further information about the origin of genetic material that had not been identified by the invasive karyotype method.…”
Section: Pre-natal Diagnosismentioning
confidence: 99%